Persistent organic pollutants in some species of the Ross Sea pelagic trophic web - CORSOLINI, S.; ADEMOLLO, N.; ROMEO, T.; OLMASTRONI, S.; FOCARDI, S. (Antarctic Science, 2003)
Adélie penguin (Pygoscelis adeliae) stomach contents, krill (Euphausia superba and E. crystallorophias) and silverfish (Pleuragramma antarcticum) from the Ross Sea were analysed to determine several persistent organic pollutants (POPs). In discussing the data, the prey-predator linkage between these species was taken into account. Sampling was carried out during the 1995/96 and 1999/00 Italian Antarctic Expeditions. Fifty four polychlorobiphenyls (PCBs) andp,p'-DDE and hexachlorobenzene (HCB) were quantified in stomach contents of penguins nesting at Edmonson Point (Victoria Land) and in whole specimens of silverfish and krill from the Ross Sea. Xenobiotic concentrations in organisms were low compared to data reported for many marine species of lower latitudes and ranged from 0.22 ng g-1 wet wt p,p'-DDE in krill to 161 ng g-1 wet wt PCBs in silverfish. Fingerprints and class of isomer patterns showed a predominance of low chlorinated PCBs, mainly in pelagic organisms. Average input of these POPs through the diet was also evaluated. Concentrations of the most toxic non-ortho PCBs, IUPAC nos 77 (3,3′,4,4′), 126 (3,3′,4,4′,5) and 169 (3,3′,4,4′,5,5′), were 1.63 pg g-1 7.31 pg g-1 and 0.23 pg g-1 wet wt, respectively, in stomach content samples. Stomach contents had 0.037 pg g-1 wet wt TEQ (Toxic Equivalents) of which penta-CB 126 accounted for most of the toxicity.